The role of acalabrutinib in adults with chronic lymphocytic leukemia - Bita Fakhri; Charalambos Andreadis (Therapeutic Advances in Hematology, 2021)
The treatment landscape of chronic lymphocytic leukemia (CLL) has significantly changed in the past decade. This paradigm shift is due to the introduction of novel agents to the field. The two major classes of drugs that have contributed to this dramatic evolution include the Bruton tyrosine kinase (BTK) inhibitors and BCL2 inhibitors. Ibrutinib was the first-in-class drug which was initially approved by the US Food and Drug Administration (FDA) for the treatment of patients with relapsed/refractory and later for patients with treatment-naïve CLL. Despite encouraging efficacy outcomes, its use has been associated with cardiovascular and gastrointestinal toxicities likely due to off-target inhibition of ITK, TEC and EGFR family kinases. The next generation of BTK inhibitors was developed to be more selective with less off-target inhibition with the prospect to improve tolerability without compromising efficacy. Acalabrutinib, a selective covalent BTK inhibitor, is a second generation BTK inhibitor. The focus of this review is on two major phase III trials that resulted in the FDA approval of acalabrutinib in 2019. The ELEVATE TN trial investigated acalabrutinib with or without obintuzumab versus chlorambucil–obinutuzumab in older and frail patients with previously untreated CLL. The ASCEND trial explored acalabrutinib versus chemoimmunotherapy in patients with relapsed/refractory CLL. Both trials demonstrated superiority of the acalabrutinib-containing arms in terms of both efficacy and tolerability. Unfortunately, the availability of new generation BTK inhibitors has not resulted in mitigating the financial toxicities associated with these potentially life-long treatments.